Eficiência das instituições federais de ensino superior brasileiras: o caso da Universidade Federal de Santa Maria - Soares, Joeder Campos (2014)
The environment Federal Institutions of Higher Education is complex. On the one hand, caution is needed when the models are not always able to reproduce dynamics that is characteristic of such organizations, on the other hand, has been demands from various agents of society for performance information of the same approach. This occurs not only in Brazil, because this is a global trend. In addition, the information on the efficiency can support the decisions of managers in the use of institutional resources, which are scarce forward demands for them. However, looking in the operating environment information such as, for example, the Management Reports of Federal Institutions of Higher Education which are components of the Annual Accoutability, they are insufficient or absent. The efficiency of the approach is relevant to the theory, as well as for operations, it is the research of resource allocation in certain alternatives over other possible employment. This dissertation about efficiency, was written to identify and analyze the behavior of the efficient use of resources from the management of an IFES, in the case UFSM, compared to other similar, the period covered between 2007 and 2012. To this we conducted an applied, non-experimental ex post facto and quantitative research. It was identified that the IFES operate with inefficiency, which is divided into technical and scale. Over time this study has already proven that UFSM characterized as IFES intermediate size. With respect to efficiency, this institution was not the most efficient IFES and not the reverse, being that their Malmquist indices indicated an improvement in total factor productivity in recent years. In addition to the results, demonstrating the efficiency scores of IFES, as the main results has the potential DEA Model on the efficient frontier of IFES approach, we get the benchmarks institutions, the slacks and the technological, efficiency and total factor productivity changes evolution.